Can India become a green superpower? The stakes of the world$1 (Bs most important energy transition s - Ghosh, Arunabha (Foreign Affairs)
When climate negotiations opened in October 2021 at the UN climate change conference of the parties in Glasgow, the environmental outlook was gloomy. Carbon emissions around the world were rapidly rising. Seemingly every part of the planet was routinely being hit with extreme weather, some of which resulted in thousands of deaths and billions of dollars in damage. But the world$1 (Bs biggest polluters were doing little to tame their emissions. The planet was on track to warm by well over two digress Celsius above preindustrial levels. It is a threshold that, if crossed, could prompt extraordinary droughts, cause the seas to inundate major coastal cities, and lead to the extinction of multiple species. s